Dynamic factorial structure of perceived condition for a women's competitive walker - Nakano, T.; Nishijima, T. (International Journal of Sport & Health Science, 2004)
The purpose of this research is to identify a dynamic factor structure of an athlete's perceived condition fluctuation using a dynamic factor analysis (DFA) and a confirmatory factor analysis (CFA). The subject of the study was an athlete who represented Japan in the women's race walking in the 2002 Asian Games. The subject made records of 15 items concerning perceived conditions, training, and basic lifestyle habits everyday for 714 days on QC sheets for conditions that she created herself. As factor analysis from an exploratory standpoint, a DFA using a maximum likelihood method and an orthogonal rotation by varimax method was applied, and common factors of perceived condition fluctuation was extracted with consideration given to time lag. Furthermore, CFA by structural equation modeling was applied to identify a dynamic factor structure of perceived condition fluctuation. Based on the coefficient of autocorrelation and the coefficient of partial autocorrelation of the variables, it was found best to use avariance-covariance matrix of Lag 1 in DFA. Three factors of weather conditions, sleeping, and getting up were extracted in all lags. However, training factor was extracted in Lag 0 only and perceived condition factor in Lag 1 only. The fit index of the dynamic factor structure model of perceived conditions where five factors were hypothesized was favorable. It was concluded that perceived condition fluctuation is a dynamic factor structure that was influenced from change in time.